Experimental and computer thermodynamics evaluations of an Al-Si-Coating on a quenchable steel - Vicente Braz Trindade; Hans-Juergen Christ (REM: International Engineering Journal)
Abstract High-strength steels are commonly used in the automobile industry in order to reduce the weight of the vehicles. However, a technical difficulty appears due to the need of hot stamping of the components, which leads to oxidation. Therefore, the application of a coating on the substrate to avoid high-temperature oxidation is used. In this work, experimental analysis and computer thermodynamic calculation were used to describe the phase transformations within an Al-Si coating on a quenchable high strength steel. The Al-Si coating was deposited by hot dipping and its characterization was done using SEM and XRD techniques. Computer thermodynamics calculations were done using the commercial software FactSage using the Calphad methodology. It demonstrated a good relationship between the experimental results and the computer calculations of phase stabilities for the as-deposited condition and after diffusion experiment at 920ºC for 7 minutes, which simulates the thermal cycle of hot stamping of the quenchable steel used.